Health Risk Assessment of Heavy Metals in Water Sources from Selected Regions in Yola North, Adamawa State, Nigeria - Stephen, Hyelda; Bassi, Wasinda Nuhu; Sirante, Richard Martin; Alli, Rejoice Monday (Journal of Multidisciplinary Science: MIKAILALSYS, 2024)
Access to clean drinking water is essential for sustainable development and human health, but heavy metal contamination poses a significant threat. This study assessed health risks linked to heavy metals in drinking and household water sources in Yola North. Water samples from surface water (Benue River), groundwater (wells and boreholes), and tap water were analysed for physicochemical properties and heavy metal content. The average daily dosage (ADD), hazard quotient (HQ), and hazard index were estimated to assess the non-carcinogenic risk (HI) and carcinogenic risk (LCR) of heavy metals from the study water sources. The physicochemical properties of water samples showed pH values within WHO limits, with temperature ranging from 23°C to 32°C, turbidity within acceptable levels, electrical conductivity varying significantly, and total dissolved solids generally meeting WHO standards. The levels of cadmium (Cd) and lead (Pb) exceeded WHO guidelines in all water samples, with the highest concentrations found in tap water (90 μg/L Cd) and surface water (210 μg/L Pb). There were considerable non-carcinogenic hazards indicated by the HQ and HI values for Pb and Cd via ingestion exceeding the threshold of 1. The LCR estimates revealed carcinogenic risks from Cd exposure in all water sources and elevated cancer risk from arsenic in surface water and tap water. Across all sources, lead presented a tolerable cancer risk. The study emphasises how critical it is to implement mitigation plans and other measures to address heavy metal contamination in the area's water sources.